2018
DOI: 10.1159/000490361
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenic Obesity: Time to Meet the Challenge

Abstract: The prevalence of overweight and obesity has reached epidemic proportions worldwide due to increasingly pervasive obesogenic lifestyle changes. Obesity poses unprecedented individual, social, and multidisciplinary medical challenges by increasing the risk for metabolic diseases, chronic organ failures, and cancer as well as complication rates in the presence of acute disease conditions. Whereas reducing excess adiposity remains the fundamental pathogenic treatment for obese individuals, complex metabolic and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(111 citation statements)
references
References 91 publications
(146 reference statements)
2
92
0
9
Order By: Relevance
“…With obesity, deleterious alterations in skeletal muscle structure and metabolism may result in declines in muscle mass and function. 154 A common belief is that patients with obesity generate larger muscular force because of the chronic overload stimulus on weight-bearing muscles. However, the body-mass normalized muscular force of patients with obesity is weaker than that of individuals with healthy body weight.…”
Section: Sarcopeniamentioning
confidence: 99%
“…With obesity, deleterious alterations in skeletal muscle structure and metabolism may result in declines in muscle mass and function. 154 A common belief is that patients with obesity generate larger muscular force because of the chronic overload stimulus on weight-bearing muscles. However, the body-mass normalized muscular force of patients with obesity is weaker than that of individuals with healthy body weight.…”
Section: Sarcopeniamentioning
confidence: 99%
“…Furthermore, with aging, increased levels of leptin, an adipocyte hormone, may result in leptin resistance and a reduction of fatty acid oxidation in muscles which contributes to ectopic fat deposition in skeletal muscle and other tissues leading to muscle atrophy [16]. Other metabolic abnormalities have been described such as mitochondrial dysfunction, muscle oxidative stress and muscle stem cell dysfunction [17].…”
Section: Pathogenesis Of Visceral and Subcutaneous Fat And Its Relatimentioning
confidence: 99%
“…This means that obesity in older age does not protect from chronic disease-related mortality when it is associated with sarcopenia. The few available studies indeed indicate that low muscle function and mass may be associated with higher mortality in obese individuals with chronic diseases [17].…”
Section: Obesity Paradox In Older Adults: Subcutaneous Fat Is the Majmentioning
confidence: 99%
“…Studies have shown that obesity is closely related to the development of diseases such as cardiovascular disease, cognitive impairment, cancer, motor disorders, and muscle mass loss (2,3). Evidence also suggests that hyperglycemia is associated with elevated fat mass, leading to increased oxidative stressors, increased pro-inflammatory factors, mitochondrial dysfunction, and ultimately cell death (4). Previous studies have shown the role of the mitochondrial pathway as one of the planned death pathways.…”
Section: Introductionmentioning
confidence: 99%